TINGKAT KEBISINGAN YANG DIHASILKAN DARI AKTIVITAS TRANSPORTASI (STUDI KASUS PADA SEBAGIAN RUAS JALAN : MANEK ROO, SISINGAMANGARAJA DAN GAJAH MADA MEULABOH) - Muhammad Kurnia; Muhammad Isya; Muhammad Zaki (Prodi Magister Teknik Sipil Unsyiah, 2018)
The increase in population has impacted on various existing resources particularly in transportation sectors. Motorized transport is one of the noise sources that could cause health problems and further interfere comfort to human. In this case, the noise level needs to be controlled based on the established quality standards as mandated by Ministry of Environment on Decree Number KEP-48 / MENLH / 11/1996 regarding Noise Level Standards. Most of the segments on Manek Roo Road, Sisingamangaraja Road and Gajah Mada Road located in Meulaboh, West Aceh District are roads located in government or private office, education and health buildings. Therefore, this study aimed to determine the noise level due to transportation activities. The study was conducted in the part of the Road and evaluated the buildings in part of Manek Roo Road, Sisingamangaraja Road and Gajah Mada Road located in Meulaboh, such as schools and hospitals to noise level concerning the standard of KEP-48 / MENLH / 11/1996. Data collection conducted in this research consist of primary data and secondary data. Primary data is data obtained directly from the observation such as traffic volume and noise level data while the secondary data obtained from the relevant agencies, and used to support the analysis. The result from the analysis reveals that the noise level due to transportation activities on the part of Road: Manek Roo, Sisingamangaraja, and Gajah Mada in Meulaboh West Aceh at 18 points of measurement is still above the quality standard (greater than 55 dBA). This noise level may disrupt the activities of schools, hospitals, etc. located along the road so that there is a need for such efforts so that the noise level received can be reduced and meet the specified quality standards.